Pigments Content (Chlorophylls, Fucoxanthin and Phycobiliproteins) of Different Commercial Dried Algae - Catarina Osório; Susana Machado; Juliana Peixoto; Sílvia Bessada; Filipa B. Pimentel; Rita C. Alves; M. Beatriz P. P. Oliveira (Separations, 2020)
Algae are a complex, polyphyletic group of organisms, affordable and naturally rich in nutrients, but also valuable sources of structurally diverse bioactive substances such as natural pigments. The aim of this work was to evaluate the polar and non-polar pigment contents of different commercial dried algae (brown: Himanthalia elongata, Undaria pinnatifida, Laminaria ochroleuca; red: Porphyra spp.; and a blue-green microalga: Spirulina spp.). The pigment extraction was carried out using different solvents (100% methanol, 100% methanol acid free, 100% ethanol, 90% acetone, N,N-dimethylformamide, dimethyl sulfoxide-water (4:1, v/v) and pH 6.8 phosphate buffer), selected according to their affinity for each class of pigments. Acetone proved to be an efficient solvent to extract chlorophylls from brown and red algae, but not from Spirulina spp. Porphyra spp. presented considerably higher levels of all pigments compared to brown algae, although Spirulina spp. presented significantly higher (p < 0.05) levels of chlorophylls, carotenoids and phycobiliproteins, compared to all macroalgae. The content of fucoxanthin extracted from the three brown algae was highly correlated to the carotenoid content. Within this group, Himanthalia elongata presented the highest fucoxanthin/total carotenoids ratio. Although the yield of extraction depended on the solvent used, the algae studied herein are an interesting source of pigments of great value for a wide range of applications.